Island of hope: migration and solidarity in the Mediterranean - Carney, Megan A. (University of California Press, 2021)
Austerity and migration as Mediterranean "questions" -- There is a lot of creativity on this island -- The reception apparatus -- Migrant solidarity work -- Edible solidarities -- Caring for the future: the case of migrant youth